Qualidade da água do Rio Cascavel - Crepalli, Mauro da Silva (2007)
The objective of this paper was establishing a water spatial temporal quality, referring the physic-chemical and bacteriological parameters in function of the discharge of the river Cascavel - PR, which are related to the soil use and occupation. The water quality of Cascavel river has been evaluated through physic-chemical parameters: dissolved oxygen (DO), electrical conductivity, pH, water temperature, turbidity, color, chemical oxygen demand (COD), nitrate, nitrite, total kejdhal nitrogen, total phosphorus and bacteriological (total and thermotolerant coliforms). For this paper achievement 2 sites set in Cascavel river basin have been select, one of them is set near the urban area and the other one is set in the basin control section. The samples collection has been carried out in periodicity of 7 days or when a significant raise of the river discharge has happened. The physic-chemical and bacteriological parameters have been analyzed according to the methodologies which are described on Standard Methods for the Examination of Water and Wastewater (APHA, 1995). The bacteriological parameters have been analyzed through the COLILERT method (cellophanes). The used tolerance limits for the analyzed parameters were the expected ones by the CONAMA resolution 357/2005. The dissolved oxygen results which have been noticed in the two sites were under the expected values by CONAMA resolution 357/2005, even a discharge raise has happened. The chemical oxygen of demand, the total and termotolerantes coliforms have show enough sensibility in order to represent higher alterations in the urban area when they show fewer discharge. In relation to the total phosphorus nutrients, nitrite and nitrate, their discharge and incorporation in Cascavel river have always been higher in the second site (agricultural area) than in the first site (urban area), however in none of these sites the established values have exceeded by CONAMA resolution 357/2005. In relation to the turbidity, color, electrical conductivity and total kejdhal nitrogen, they have not shown sensible themselves to differentiate the water quality alteration from Cascavel river which has been provoked by the urban and agricultural use, showing, however, a strong correlation to an discharge, thus leading to compromise hereafter the water quality from the river in study progress.